Penyalahgunaan Perusahaan Cangkang dalam Tindak Pidana Pencucian Uang Berbasis Kejahatan Sumber Daya Alam - Audry Salsabila Pasaribu; Ahmad Hamdani; Muhamad Radjhu Khan Saputra; Muhamad Rifki Nurrasman; Margo Hadi Pura; Puti Priyana (Science and Education Journal (SICEDU), 2026)
The abuse of shell companies in Money Laundering Crimes (TPPU) based on natural resource crimes represents an organized white-collar crime modus operandi that exploits corporate legal fiction to sever the chain of criminal evidence. This study aims to analyze the legal standing of shell companies as strategic instruments for concealing the origin of illicit assets and to examine the construction of proving criminal liability against the actors controlling them. The research method employed is normative juridical, utilizing statutory, conceptual, and case study approaches. The results indicate that shell companies serve as artificial legal shields devoid of economic substance, facilitating the layering and integration phases through capital legality engineering, nominee agreements, and import-export transaction manipulations to conceal the identity of the Beneficial Owner. Proving criminal liability against corporate controllers requires disregarding the legal fiction of separate personality through the doctrine of piercing the corporate veil and the alter ego theory. Pursuant to Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering jo. Law Number 1 of 2023 on the Criminal Code, criminal sanctions can be applied cumulatively to both the controlling individuals and the shell corporations.